Hardening of bucket teeth made from creusabro 8000 steel by using the induction hardening method - Darma Firmansyah Undayat; Cecep Ruskandi; Ari Siswanto (Politeknik Negeri Lhokseumawe, 2023)
Excavators are often used in mining projects such as for penetrating, excavating, dredging, gouging, and crushing mineral rocks. Bucket teeth are an excavator component that is often being replaced due to failure. The most common failure mode that occurred in bucket teeth was wear on the tip or front section of it. To reduce the wear of the bucket teeth material then its hardness should be increased. As the hardness value increases, the resistance to wear increases. The bucket teeth were made of Creusabro 8000 steel and a hardening process was then carried out on the front section of the bucket teeth components by using an induction furnace. The power used in the induction furnace varies from 28, 35, 42 and 49 kW (kilowatts) and the holding time varies between 3 and 5 minutes. The heat treatment process used oil as a cooling medium. The analysis was carried out to determine the area that experienced an increase in hardness and its occurred microstructure. Microstructure examination was carried out with an optical microscope, and hardness test by using a Vickers microscopy. It can be concluded from the result of the analysis that the large area experienced an hardness increase is directly proportional to the electric current magnitude and holding time. The microstructure has changed from fine pearlite to martensite thus hardness of Bucket Teeth can be increased up to 100% of the initial hardness.